PREPARATION OF REINFORCED POLYMER-BITUMEN COMPOSITIONS FOR ROADS - Buriyev A. P.; PhD Djurayev V. N.; PhD Makhkamova L. K.; Assistant Erkinov H.G. (Web of Journals Publishing, 2025)
The integration of polymer additives into bitumen has significantly enhanced the performance and durability of road pavements. This article explores the preparation methods, chemical interactions, and benefits of reinforced polymer-bitumen compositions in road construction. By examining various polymer types and their effects on bitumen properties, the study aims to provide insights into the development of high-performance road materials.
Keywords: Polymer-modified bitumen, road construction, bitumen reinforcement, polymer additives, pavement durability, chemical composition.